Savings of the poor : how they do it-- - Datta, Sankar; Narayana, S. L.; Srinivas, S.; BASIX (Firm); LivelihoodSchool (Hyderabad, India) (Bangalore : Books for Change, 2010)
Contributed articles presented at a workshop, held at Hyderabad, during 2-3 May 2008.
"BASIX, Livelihood School."
Includes bibliographical references.
Keywords: Saving and investment -- India -- Congresses; Poor -- India -- Finance, Personal -- Case studies -- Congresses; Savings accounts -- India -- Congresses; Savings accounts -- Congresses